2003
DOI: 10.1071/sr02044
|View full text |Cite
|
Sign up to set email alerts
|

The effect of soil texture and roots on the stable carbon isotope composition of soil organic carbon

Abstract: This study examines the distribution of soil organic carbon and carbon-isotopes with depth and among particle size fractions in 2 forest soil profiles of contrasting texture from Cape York Peninsula, Queensland, Australia. The profile on sand has a comparatively low inventory of carbon (557 mg/cm2 from 0–100 cm) and exhibits comparatively small variations in δ13C value. In contrast, the clay-rich profile has a much larger inventory of soil organic carbon (1725 mg/cm2 from 0–100 cm) and large variations in δ13C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
49
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 52 publications
6
49
3
Order By: Relevance
“…These results are consistent with those reported by other authors, e.g. Nadelhoffer and Fry (1988), Accoe et al (2003) and Bird et al (2003). The results of a litter bag experiment led Connin et al (2001) to suggest that mechanisms responsible for isotopic discrimination are, at least partly, characteristic of earlier decay stages.…”
Section: And N Distribution In Som Fractionssupporting
confidence: 94%
“…These results are consistent with those reported by other authors, e.g. Nadelhoffer and Fry (1988), Accoe et al (2003) and Bird et al (2003). The results of a litter bag experiment led Connin et al (2001) to suggest that mechanisms responsible for isotopic discrimination are, at least partly, characteristic of earlier decay stages.…”
Section: And N Distribution In Som Fractionssupporting
confidence: 94%
“…By contrast, in samples with smaller SSA, which presumably contain less protective mineral phases, HF treatment released predominantly 13 C-depleted organic constituents. This finding agrees with the view that potentially biodegradable compounds enriched in 13 C such as polysaccharides and proteins can be stabilized by mineral surfaces (Bird et al 2003;Kiem and Ko¨gel-Knabner 2003) and are thus effectively removed during mineral dissolution (Dai and Johnson 1999;Schmidt and Gleixner 2005).…”
Section: Mineral-protected Organic Mattersupporting
confidence: 89%
“…This would lead to depletion of δ 13 C in soil organic matter relative to the starting litter inputs, at least in the early stages (e.g., Flanagan et al 1999;Garten et al 2000;Quideau et al 2003). However, numerous studies (e.g., Buchmann et al 1997;Flanagan et al 1999;Ehleringer et al 2000;Feng 2002;Bird et al 2003;Quideau et al 2003) have shown that decomposition of organic matter is associated with increasing δ 13 C. The δ 13 C value usually increases with soil depth or with decreasing particle-size fraction within a depth range, as soil organic matter becomes increasingly dominated by microbial necromass stabilized by mineral association (Bird et al 2003).…”
mentioning
confidence: 99%